The analysis of acne increasing suicide risk. Issue 24 (18th June 2021) - Xu, Shuangyan; Zhu, Yun; Hu, Hu; Liu, Xiuhong; Li, Li; Yang, Binbin; Wu, Wei; Liang, Zuohui; Deng, Danqi
Abstract : Abstract: Acne is associated with depression and anxiety; however, the relationship between acne and suicide is still unclear. This study is aimed to evaluate the association between acne and suicide by conducting a meta-analysis. Studies were identified by electronic searches of the PubMed and EMBASE databases from their inception through Jan 10, 2020. Two authors separately assessed the quality and extracted data from the selected studies. When the heterogeneity was significant, we used a random-effects model to calculate overall pooled risk estimates. Five studies involving a total of 2, 276, 798 participants were finally included in the meta-analysis; 52, 075 participants had acne. Suicide was positively associated with acne in the overall analysis (odds ratio (OR) 1.50, 95% confidence interval (95% CI): 1.09–2.06, P = .004, I 2 = 74.1%). Subgroup analyses were performed for suicidal behavior groups ( P = .002, I 2 = 80.4%), suicidal ideation or thoughts groups ( P = .849, I 2 = 0.0%), International Classification of Diseases version 9 (ICD-9) groups ( P = .137, I 2 = 49.6%), non-ICD-9 groups ( P = .950, I 2 = 0.0%), American groups ( P = .311, I 2 = 2.4%), and non-American groups ( P = .943, I 2 = 0.0%). Sensitivity analyses indicated flawed results. No publication bias was detected. Acne may significantly increase suicide risk. Clinicians should actively treat acne and consider suicide screening. Further international studies with high-quality analyses are needed as more data are published. Ethical approval and patient consent are not required because this study is a literature-based study.